The Role of Organic Extracts and Inorganic Compounds as Alleviators of Drought Stress in Plants - Pedro Garcia-Caparros; Michele Ciriello; Youssef Rouphael; Maria Giordano (Horticulturae)
Climate changes have exacerbated the progression of drought conditions on a global scalethreating to crop production and heightening concerns over food security. Water scarcity enforces alterations in fundamental morphology, physiology and biochemical traits in crops. Consequently, it is imperative to identify environmentally sustainable alternative solutions to mitigate this problem and enhance overall plant performance. In this sense, biostimulants have emerged as a promising alternative as they improve plant resilience, enhance physiological processes, and mitigate the detrimental consequences of water deficit conditions on crop production. This review compiles the latest research on the application of organic extracts and inorganic compounds in crops subjected to drought conditions, specifically humic acids, protein hydrolysates, seaweed extracts, and silicon. Moreover, it offers a comprehensive overview of the origins and effectiveness of these biostimulants, with a detailed analysis of their application and the associated physiological, biochemical, and genetic modifications induced by these bioactive compounds. This knowledge enhances the understanding of the efficacy and implementation strategies pertinent of these compounds under water stress scenarios in agricultural settings.